Integrasi Nilai Ekoteologi Islam dalam Pendidikan Agama Islam: Studi Kasus di MTs Al-Ichsan Nanggulan, Kulon Progo, Yogyakarta - Fatmawati; Handayana Rehan Pratama; Adjie Fahrezy Husaini; Inayatun Nupus (BAYAN: Jurnal Studi Islam dan Humaniora, 2025)
The relationship between faith and ecological responsibility in studying Islamic religious education (PAI) is very close. In Islam, faith is not only related to spiritual and ritual aspects, but also includes responsibility  towards  the  environment.  Based  on  Islamic  ecotheology,  PAI  teachings  contain environmental care values originating from the Al-Quran and Hadith. The aim of this research is not only in the cognitive realm, but also concerns increasing awareness, attitudes, behavior, skills and  participation  that  lead  to  environmentally  responsible  morals  and  ethics  at  MTs  Al-IchsanNanggulan. The planned learning strategy must implement aspects of learning materials, learning strategies and models, as well as support from educational institutions to achieve these goals. This research uses a qualitative approach with observation and interview methods. And there are many references taken from various journals, books and previous research results related to this problem. It is hoped that the results of this research will contribute conceptually and become an inspiration for the development of praxis.